2011
DOI: 10.1371/journal.pone.0021666
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipids and Betaine Are Related in an Acute Coronary Syndrome Cohort

Abstract: BackgroundLow plasma betaine has been associated with unfavorable plasma lipid profiles and cardiovascular risk. In some studies raised plasma betaine after supplementation is associated with elevations in plasma lipids. We aimed to measure the relationships between plasma and urine betaine and plasma lipids, and the effects of lipid-lowering drugs on these.MethodologyFasting plasma samples were collected from 531 subjects (and urine samples from 415) 4 months after hospitalization for an acute coronary syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 38 publications
11
46
0
Order By: Relevance
“…Associations of choline and betaine with diabetes have also been made by several groups [42, 53, 56, 57]. Moreover, several studies have observed increased levels of choline and betaine associated with the increased incidence of coronary syndrome as well as increased blood lipid levels [39, 40, 42, 5862]. This provides evidence for the relationship between choline and betaine with diabetes and cardiovascular health.…”
Section: Microbiota Produced Metabolites and The Evolving Relationshimentioning
confidence: 55%
“…Associations of choline and betaine with diabetes have also been made by several groups [42, 53, 56, 57]. Moreover, several studies have observed increased levels of choline and betaine associated with the increased incidence of coronary syndrome as well as increased blood lipid levels [39, 40, 42, 5862]. This provides evidence for the relationship between choline and betaine with diabetes and cardiovascular health.…”
Section: Microbiota Produced Metabolites and The Evolving Relationshimentioning
confidence: 55%
“…For example, a study of a cohort with acute coronary syndrome concluded that high and low plasma betaine concentrations were associated with increased risks of secondary heart failure and acute myocardial infarction, respectively (24). A second study in the same cohort concluded that lower plasma betaine concentrations were associated with higher concentrations of triglycerides and non-HDL cholesterol (25). In contrast, in the NAME population, although there was an inverse relation between plasma betaine and both LDL-cholesterol and triglyceride concentrations, there was no significant relation between plasma betaine concentrations and odds of cardiovascular or cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were also excluded if their glycated haemoglobin (HbA 1c ) was >9.5% (80 mmol/mol) or they had had renal disease (estimated glomerular filtration rate [eGFR] <60 ml/min/ 1.73 m 2 or urine albumin:creatinine ratio [UACR] >30 mg/mmol), abnormal liver enzymes, heart failure, known active malignancy or myocardial infarction in the preceding six months. Details of variables such as weight, plasma glucose, HbA 1c and markers of renal failure throughout the study were previously reported by Krebs et al 12 Because fibrates have been associated with increased urinary betaine excretion, [13][14][15] subjects who were on fibrate therapy were excluded from the analysis. …”
Section: Methodsmentioning
confidence: 99%